2022
DOI: 10.1155/2022/6851900
|View full text |Cite
|
Sign up to set email alerts
|

Application of Prognostic Models Based on Psoas Muscle Index, Stage, Pathological Grade, and Preoperative Carcinoembryonic Antigen Level in Stage II-III Colorectal Cancer Patients Undergoing Adjuvant Chemotherapy

Abstract: Objective. To investigate the effect of sarcopenia on the prognosis of stage II-III colorectal cancer patients undergoing adjuvant chemotherapy. Methods. A total of 196 stage II-III colorectal cancer patients who received 8 cycles of postoperative chemotherapy were retrospectively analyzed. An abdominal CT acquired at 3-4 weeks after surgery was used to calculate the psoas muscle index. Subsequently, once gender-specific receiver operating characteristic curves were plotted and cut-off values of psoas muscle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…These results suggest that non‐sarcopenic elderly patients selected for AC generally have a better prognosis. The presence of sarcopenia before AC has been associated with a poor prognosis compared with the absence of sarcopenia 28 . This study also showed no benefit of AC in patients with sarcopenia.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…These results suggest that non‐sarcopenic elderly patients selected for AC generally have a better prognosis. The presence of sarcopenia before AC has been associated with a poor prognosis compared with the absence of sarcopenia 28 . This study also showed no benefit of AC in patients with sarcopenia.…”
Section: Discussionmentioning
confidence: 43%
“…The presence of sarcopenia before AC has been associated with a poor prognosis compared with the absence of sarcopenia. 28 This study also showed no benefit of AC in patients with sarcopenia. In contrast, non‐sarcopenic elderly patients have found AC as useful as non‐elderly patients.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In our previous study, we have reported the prognostic significance of PMI in patients with hepatocellular carcinoma undergoing radiofrequency thermal ablation and pancreatic cancer undergoing systemic chemotherapy 34 , 35 . PMI well predicts prognosis in patients with colorectal cancer 36 . PMI can be helpful for predicting postoperative outcomes in patients with esophageal cancer undergoing surgery 37 .…”
Section: Discussionmentioning
confidence: 93%
“…The association between high CEA levels and cancer is widely known in the medical community [ 29 ]. Previous studies have demonstrated that up to one-third of patients with CRC develop sarcopenia [ 30 ]. Despite the frequent coexistence of high CEA levels and LMM in the cancer population, no study has assessed whether this coexistence is mediated by cancer or the possibility of a direct relationship between CEA levels and low muscle mass.…”
Section: Discussionmentioning
confidence: 99%